The risk assessment of Lead, Cadmium and Zinc in the two edible fishe species (Carcharhinus limbatus) and (Epinephelus coioides) of Persian Gulf in 2016 - Parisa Dadkhah; Atefeh chamani; Samar Mortazavi (Pizhūhish dar Bihdāsht-i Muḥīṭ., 2018)
Abstract   Background and aim:With the development of coastal industries and cities, aquatic ecosystems and organisms are exposed to contaminants, especially heavy metals. Heavy metals accumulate in aquatic tissues and eventually enter the food chain and human body. The aim of this study was to investigate the concentrations of lead, cadmium and zinc in muscle of two fish species (Cicharhinuslimbatus) and (Epinepheluscoioides) from the Persian Gulf.   Materials and Methods:For this purpose, 15 samples of muscle were takenfrom each fish, and by wet digestion method, the concentration of Lead, Cadmium and Zinc were measured by atomic absorption device. Statistical analysis of the obtained results was carried out by SPSS software (v.20) using Shapiro-Wilk, One Sample T-Test and Binomial Test.   Results:According to the results, the mean concentrations of lead, zinc and cadmium were 5.55, 8.40, 0.202 mg/kg and 14.9, 13.54, 277.0 mg/kg, in Cicharhinuslimbatus and Epinepheluscoioides respectively. The mean concentration of lead in both fisheswashigher than the WHO standard. The HI index for Cicharhinuslimbatus and Epinepheluscoioides is less than 1.   Conclusion:With respect to the obtained results, the absorption of these metals does not threaten consumers. However, the proportions of condition factor for Cicharhinuslimbatus and Epinepheluscoioides are not within the standard range and indicate the inappropriate conditions of this habitat for aquatic health and environmental stresses.